Comparative Efficacy of Biologic Agents in the Treatment of Moderate to Severe Psoriasis - Giri, Atul; Katalakute, Shivani; Somvanshi, Tejaswini (Journal of Neonatal Surgery, 2025)
Background: Moderate to severe psoriasis significantly impairs quality of life and requires effective systemic therapies. Biologic agents targeting different immune pathways have transformed treatment but comparative efficacy data are limited. Aim: To compare the efficacy, safety, and quality of life outcomes of Secukinumab, Adalimumab, and Ustekinumab in patients with moderate to severe psoriasis. Methods: An observational study including 60 patients treated with Secukinumab (n=21), Adalimumab (n=19), or Ustekinumab (n=20) was conducted over 24 weeks. Baseline demographics, Psoriasis Area and Severity Index (PASI), body surface area (BSA), and Dermatology Life Quality Index (DLQI) were recorded. Clinical response was assessed by PASI 75 achievement, time to response, and safety profiles were monitored. Quality of life was evaluated by DLQI score changes. Results: All biologics demonstrated significant clinical efficacy with PASI 75 rates of 71.4%, 57.9%, and 80.0% for Secukinumab, Adalimumab, and Ustekinumab, respectively (p=0.31). Time to PASI 75 was significantly shorter with Secukinumab and Ustekinumab (p=0.05). Adverse event rates were comparable across groups. Quality of life improvement was significantly greater with Secukinumab and Ustekinumab compared to Adalimumab (p=0.003). Conclusion: Secukinumab and Ustekinumab showed trends towards faster and greater clinical and quality of life improvements compared to Adalimumab, with all agents maintaining favorable safety profiles. These findings support the use of IL-17 and IL-12/23 inhibitors as effective options in moderate to severe psoriasis